Maintenance Culture and the Challenges of Infrastructural Development in Nigeria: Implications for the Welfare of the Citizenry in the Fourth Republic - Manjo, Yusuf Garba (Kashere Journal of Politics and International Relations, 2023)
In developed climes, policy makers and civil servants usually put in place an appropriate maintenance scheme for sustenance of public infrastructural facilities in their country. However, in Nigeria’s fourth republic between 1999 and 2023, reverse is the case; as adequate maintenance of public infrastructure has not been given the deserved attention by federal, state and local governments in the country. Notwithstanding this, successive governments at federal, state and local levels in the country always budgeted huge sums for overheads and maintenance costs which are rarely carry out on these facilities. To discover the fact, survey and participant observatory methods as well as secondary data were employed. The paper found that the factors responsible for poor management of infrastructural facilities include: poor leadership, corruption, bad attitude of citizens to public infrastructure facilities, insufficient of maintenance workers, insufficient fund and shortage of maintenance materials, among others. The paper also found that the poor maintenance of public infrastructure has adversely affected the life span of public utilities in the country. As a way forward, it recommended that national maintenance policy should be formulated, facility management agency should be created across ministries, departments and agencies of government to periodically carry out maintenance scheme for public infrastructural facilities to enable them be in good condition at all times, for the welfare of the citizenry.